Involving Students in the Prevention and Handling of Sexual Violence in Universities (Study of the Effectiveness of Sexual Violence Regulation in Lampung Universities) - Murdiana, Elfa; Dela Oktora, Nency; Yenti, Zarfina; Mahmudah, Nurul; Talib Ibrahim, Muhammad (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
This article aims to answer about the role and obstacles faced by students in preventing and handling sexual violence in universities in Lampung. By using qualitative methods and a philosophical approach and cultural approach, it is known that Article 24 paragraph 3 and Article 27 (Permendikbud Number 30 of 2021 stipulate strict rules governing student participation in the prevention and handling of sexual violence (PPKS) in public universities. In religious universities, the involvement of students in the prevention and handling of sexual violence is regulated in the Decree of the Director General of Pendis Number 1143 of 2024 concerning PPKS Technical Guidelines at PTKI, chapter III letter B. Based on the interview techniques carried out, it is known about the obstacles faced in mainstreaming the role of students in PPKS. The implementation of student involvement in preventing and handling sexual violence in higher education is still limited to the process and mechanism of socialization and education. This means that legal awareness of the role mandated by legal regulations is only at the level of growing knowledge. On the other hand, university facilities and infrastructure also contribute to reducing the role of students in PPKS So that universities must continue to strive to optimize student involvement in various programs that support the mechanism for preventing and handling sexual violence and continue to fight for the presence of PPKS facilities and infrastructure to realize a college without sexual violence.